The Demographic Transition in Closed and Open Economies: A Tale of Two Regions - Giovanni L. Violante; Orazio P. Attanasio (Inter-American Development Bank, Research Department, 2000)
This paper constructs a general equilibrium overlapping generation model to evaluate quantitatively how demographic transition (falling mortality and fertility rates) affects aggregate variables (wages, interest rate, output), and inter-generational welfare in closed and open economies. We perform this analysis for two economies calibrated to resemble the North (US and Europe) and Latin America. Our simulations suggest that the demographic transition could have generated income per capita growth up to 0. 5% per year in excess of steady-state growth in the past 50 years in Latin America and 0. 3% in the North.
Keywords: 330; Offene Volkswirtschaft; Overlapping Generations; Wohlfahrtsanalyse; Nordamerika; Europa; Lateinamerika; Demographischer Übergang